Innovative Technical Solution Using the Renal Artery Stump after Nephrectomy as an Inflow Artery for Lower Limb Revascularization—A Case Report - Russu, Eliza; Mureșan, Adrian Vasile; Kaller, Reka; Toma, Lucian; Coșarcă, Cătălin Mircea; Chibelean, Călin Bogdan; Arbănași, Emil Marian; Arbănași, Eliza Mihaela (Frontiers in Surgery, 2022)
We present the case of a 56-years-old patient admitted to the vascular unit of Targu Mures County Emergency Clinical Hospital after a computed tomography angiography (CT angiography) performed for critical limb ischemia showed a tumor of the right kidney of 11,3/12/11 cm anteroposterior/later-lateral/craniocaudal (AP/LL/CC), accompanied by an abdominal aortic aneurysm (3 cm diameter) and right iliac artery occlusion. An interdisciplinary team formed of urological and vascular surgeons decided and performed a one-step operation. The right kidney was removed, and the limb revascularization was achieved by performing a bypass that used the right renal arterial stump as an inflow artery, thus a reno-femoral bypass. The abdominal aortic aneurysm had no indication for reconstruction. The final pathology interpretation of the kidney tumor revealed a clear cell renal cell carcinoma, excised with oncological safety margins. Short-term follow-up found the patient without ischemic symptomatology and the fully functional graft.